2022
DOI: 10.3389/fnmol.2021.807090
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of KCC2 in Parvalbumin-Positive Interneurons Is Associated With a Decreased Seizure Threshold and a Progressive Loss of Parvalbumin-Positive Interneurons

Abstract: GABAA receptors are ligand-gated ion channels, which are predominantly permeable for chloride. The neuronal K-Cl cotransporter KCC2 lowers the intraneuronal chloride concentration and thus plays an important role for GABA signaling. KCC2 loss-of-function is associated with seizures and epilepsy. Here, we show that KCC2 is expressed in the majority of parvalbumin-positive interneurons (PV-INs) of the mouse brain. PV-INs receive excitatory input from principle cells and in turn control principle cell activity by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 105 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…A hypothesis to explain this result is that these animals may have developed reactive astrogliosis ( Khurgel et al, 1995 ; Cole-Edwards et al, 2006 ). This hypothesis is based on the premise that, unlike KCC2, which is expressed exclusively in neurons ( Papp et al, 2008 ; Moore et al, 2017 ; Herrmann et al, 2021 ), NKCC1 is also largely present in astrocytes ( Khirug et al, 2008 ; Löscher et al, 2013 ; Virtanen et al, 2020 ). Extensive data has shown that the animal models of epilepsy mentioned earlier rapidly develops reactive astrogliosis in the brain, either directly, as in the KA-SE model ( Vargas et al, 2013 ), or indirectly, as the pilocarpine-induced SE ( Shapiro et al, 2008 ), and in EK ( Khurgel et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A hypothesis to explain this result is that these animals may have developed reactive astrogliosis ( Khurgel et al, 1995 ; Cole-Edwards et al, 2006 ). This hypothesis is based on the premise that, unlike KCC2, which is expressed exclusively in neurons ( Papp et al, 2008 ; Moore et al, 2017 ; Herrmann et al, 2021 ), NKCC1 is also largely present in astrocytes ( Khirug et al, 2008 ; Löscher et al, 2013 ; Virtanen et al, 2020 ). Extensive data has shown that the animal models of epilepsy mentioned earlier rapidly develops reactive astrogliosis in the brain, either directly, as in the KA-SE model ( Vargas et al, 2013 ), or indirectly, as the pilocarpine-induced SE ( Shapiro et al, 2008 ), and in EK ( Khurgel et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the OpK model induces some level of epileptogenesis, and the loss of PV-INs from OpK can be more severe and extensive compared to previous reports which found only mild PV-INs loss ipsilaterally ( Ryu et al, 2021 ). The chronic loss of PV-INs may also be associated with the chronic disruption of KCC2, via mitogen-activated protein kinase- (MAPK) dependent apoptosis ( Herrmann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, disruptions in GABAergic interneurons in cortex have been implicated in several neurological conditions including Alzheimer's Disease [10][11][12] , schizophrenia 13,14 , autism spectrum disorder 15,16 , and epilepsy [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…GABAergic interneurons provide a break on excitation, control timing and synchrony within neural circuits 47 , and can be modulated differentially according to cell class 8,9 . Moreover, disruptions in GABAergic interneurons in cortex have been implicated in several neurological conditions including Alzheimer’s Disease 1012 , schizophrenia 13,14 , autism spectrum disorder 15,16 , and epilepsy 1719 .…”
Section: Introductionmentioning
confidence: 99%